Hak Waris Anak Perempuan di Cimanuk (Antara Kompilasi Hukum Islam dan Penetapan Pengadilan Agama Nomor 69/Pdt.P/2013/Pdlg) - Somawinata, Yusuf; Taqiyuddin, Hafidz (Institut Agama Islam Negeri Curup, 2020)
This research was to explore the importance of the inheritance rights of women towards the inheritance rights of deceased brothers who were applied in the Pandeglang district, Banten. The object of this research is inheritance law in the Islamic Law Compilation. The secondary source of this research is the Religious Court Decision Number 69/Pdt.P/2013/PA.Pdlg. The interviews related to this research were conducted in Cimanuk sub-district, Pandeglang district. This research is a collaborative research of library and field research which is qualitative model. The collected data is processed by selecting and classifying data. Then the data is analyzed by comparing and interpreting. This study found that in general, the Cimanuk ulama or community leaders gave the asabah (remaining assets) portion to deceased brothers or sisters, both siblings and brothers who inherited along with the daughters. However, there are also those who argue that a brother or sister, both siblings and a father is veiled by a daughter, so that they do not get part of the inheritance inheritance. It was also found that in principle the determination had been made by the people of Cimanuk sub-district. The conclusion of this study is the provisions in the Pandeglang Religious Court Decision Number 69/Pdt.P/2013/PA.Pdlg. November 7th, 2013 shows the difference with the provisions in the Islamic Law Compilation. KHI has a stipulation that girls do not prevent (hijab) their brothers,inheritance right, while the Religious Court rulings show that girls can obstruct the inheritance rights of brothers.